International Financial Statistics Yearbook, 2015. (International Financial Statistics; International Financial Statistics, 2015)
This paper presents the International Financial Statistics (IFS) 2015 yearbook. The monthly printed issue of IFS reports current monthly, quarterly, and annual data, while the yearbook reports 12 observations of annual data. Most annual data on the CD-ROM and Internet begin in 1948; quarterly and monthly data generally begin in 1957; most balance-of-payments data begin in 1970. The different sections describe conceptual and technical aspects of various data published in IFS. The reader will find more detailed descriptions-about coverage, deviations from the standard methodologies, and discontinuities in the data-in the footnotes in the individual country and world tables in the monthly and yearbook issues of IFS, in the Print_Me file on the CD-ROM, and in the PDF pages on the Internet. Data on members' Fund accounts are presented in the Fund Position section in the country tables and in four world tables.